2018
DOI: 10.23969/jrbm.v11i2.1256
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aims to determine the influence of good corporate governance mechanism proxied with managerial ownership, institutional ownership, independent board of commissioners and audit committee, profit management condition as measured by discretionary accruals and financial performance as measured by return on assets mining company period 2012-2016. The sample are 11 companies. This research uses descriptive and verificative method using panel data regression analysis. The result shows that good corporate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
2
1
1
Order By: Relevance
“…This is in line with research conducted by Marini and Marina (2017), Setiawan and Setiadi (2020) and Adi and Suwarti (2022) which concluded that the number of audit committees in the company does not guarantee that the company's financial performance will improve. This result is different from the research conducted by Abduh and Rusliati (2018), Suryanto and Refianto (2019) and Amelinda and Rachmawati (2021) which concluded that the audit committee affects the company's financial performance.…”
Section: R Squarecontrasting
confidence: 96%
See 3 more Smart Citations
“…This is in line with research conducted by Marini and Marina (2017), Setiawan and Setiadi (2020) and Adi and Suwarti (2022) which concluded that the number of audit committees in the company does not guarantee that the company's financial performance will improve. This result is different from the research conducted by Abduh and Rusliati (2018), Suryanto and Refianto (2019) and Amelinda and Rachmawati (2021) which concluded that the audit committee affects the company's financial performance.…”
Section: R Squarecontrasting
confidence: 96%
“…The results of this study are in line with previous research conducted by Marini and Marina (2017), Abduh and Rusliati (2018) and Setiawan and Setiadi (2020) which concluded that the independent board of commissioners has an influence on financial performance as measured using ROA. Meanwhile, this study is different from the results of research conducted by Suryanto and Refianto (2019), Sari et al, (2019) and Adi and Suwarti (2022) which concluded that the more independent commissioners, the company's financial performance did not increase because the duties of the independent board of commissioners can only provide advice and have little impact on the company's financial statements.…”
Section: R Squaresupporting
confidence: 91%
See 2 more Smart Citations
“…Kepemilikan manajerial adalah jumlah kepemilikan atas saham oleh pihak manajemen dari seluruh modal saham perusahaan (Abduh & Rusliati, 2018). Penelitian yang dilakukan oleh Cahyadi dan Mertha, (2019) menyatakan bahwa kepemilikan manajerial berpengaruh negatif terhadap manajemen laba.…”
unclassified